Peningkatan Hasil Belajar Terpadu Siswa Menggunakan Problem-Based Learning Berbantuan Media Powtoon di Kelas V Sekolah Dasar - Muzakki, Adib; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research was conducted because in integrated thematic learning, students' learning outcomes are very low. The research aims to describe the use of the Problem-Based Learning model in the learning process to improve learning outcomes. The research was conducted in 2 cycles. The four stages in the research procedure consist of planning, implementation, observation and reflection. Observation sheets, test sheets and non-tests are instruments for data collection. The results showed an increase in a) RPP cycle I 81.9% sufficient qualifications and cycle II 94% very good qualifications, b) Implementation of the learning process aspects of teachers and students cycle I 82% good qualifications and cycle II 96% very good qualifications, c) The results of the assessment of students in improving learning outcomes in cycle I obtained an average of 76.5% sufficient qualifications and cycle II 85% very good qualifications. Thus, it can be concluded that the Powtoon-assisted PBL model can improve the learning outcomes of students in integrated thematic learning in class V.